Ussulu: Interferensi Agama Masyarakat Muslim Di Kabupaten Maros - Muhammad Idris (Universitas Islam Negeri Alauddin Makassar, 2014)
This paper discusses the essence of religion in Islam, especially regarding the procedure to implement the teachings of Islam in accordance with the Five Pillars of Islam. The Five Pillars of Islam are: pronounce the shahadah, praying prayers, alms issued, and pilgrimage for those who can afford. It is the bedrock of the Muslim community in Maros as adherents of the congregation Ussulu community. Congregation Ussulu is meant by the Muslim community in the area is a teaching that is considered to be a guide in the teachings of Islam. Congregation Ussulu it becomes a religious guidelines that are considered permanent in life in religion (Islam). It is argued that the teachings carried forth in the art will be a guarantee for anyone who embraces the congregation would survive the world and in the hereafter.